Цифрові технології управління публічними фінансами: податковий аспект - Глущенко, Ольга Вікторівна; Хмельков, Андрій Володимирович; Дячек, Ольга Юріївна; Бабаєв, Валерій Юрійович; Громов, Сергій Олександрович; Hlushchenko, Olha; Khmelkov, Andrii; Diachek, Olga; Babaiev, Valerij; Gromov, Sergey (Київ : ДКС Центр, 2024)
У статті здійснена спроба переосмислення фунтаментальних теорем оподаткування у контексті формування парадигми діджиталізації та менеджменту публічних цінностей. Запропоновано низку висновків та пропозицій щодо трансформації податкової системи цифрової епохи, а також новітніх технологій управління публічними фінансами. Завдяки впровадженню більш складних податкових систем для більш цілеспрямованого перерозподілу доходу та збору все більш достовірної інформації про економічні результати діяльності платників податків цифрізація може покращити технологію стягнення податків. Таким чином, діджиталізація може дозволити знизити ставки податків, щоб зібрати або перерозподілити той самий обсяг доходу, який вони отримують за допомогою поточних податкових систем. Цифровізація піднімає питання щодо захисту приватного життя громадян і якості державних установ. Діджиталізація може підвищити податкові системи, підвищити економічну ефективність і сприяти справедливості в країнах, де верховенство права, добре функціонує демократія та сувора захист приватного життя.

The article attempts to rethink the fundamental theories of taxation in the context of the development of the paradigm of digitalisation and the management of public values. The authors offer a number of conclusions and proposals for the transformation of the tax system in the digital age and the latest public finance management technologies. By implementing more sophisticated tax systems to better target income redistribution and collecting increasingly reliable information on the economic performance of taxpayers, digitalisation can improve tax collection technology. As such, digitalisation may allow governments to lower tax rates to collect or redistribute the same amount of revenue as they do through current tax systems. Digitalisation can provide more data on people's consumption, such as through the use of digital payment methods and a gradual shift away from cash. It can also help to inform and improve the links between ownership and capital income, including dividends, capital gains, property income, and pension accruals. Additionally, international registries of asset ownership and capital income can be created to automate and improve international information exchange. Financial institutions are well-suited to act as third-party reporters of income and wealth to governments. For instance, consumers can report VAT or sales taxes as third parties by using electronic payment information, such as credit and debit cards, thanks to digitalisation. Capital gains can be taxed on a residence basis, according to international asset and shareholder registries, rather than a source basis. Corporate income tax can be eliminated or used as a dividend tax. Digitalisation raises questions about the protection of citizens' privacy and the quality of public institutions. It can improve tax systems, increase economic efficiency, and promote equity in countries with a rule of law, well-functioning democracy, and strong privacy protections. However, in countries with high levels of corruption, authoritarian regimes, weak institutions, a weak or non-existent rule of law, and where digitalisation does not guarantee the protection of citizens' privacy, digitalisation may prove to be ineffective.
Fiscal aspects of digital technologies for public finance management
Keywords: SOCIAL SCIENCES::Business and economics; публічні фінанси; цифрове врядування; смарт-контракти; public finance; digital governance; smart contracts; місцеві фінанси; механізм управління; публічні послуги; цифрові технології; local finance; mechanism of administration; public services; digital technologies